(untitled) (Colombia Medica, 1986)
G-6PD deficiency affects a great number of people in many countries of the world. Since in the American Continent, the disease is most commonly found in black males, 150 black Colombian men were studied with a simple but precise screening test. Nineteen patients, i.e., 12.7% of the sample, were positive. This figure is very similar to several reports from other parts of the country and America. Some aspects of the disease and its clinical expression are briefly considered.